Enhancing Elementary School Students’ Learning Outcomes in the Field of Social Sciences Studies through Problem Based Learning Method - Sita Ratna Ningsih; Mohamad Syarif Sumantri; Nurjanah Nurjanah; Erry Utomo (AT-TA'LIM, 2019)
The learning outcomes of the Social Sciences study at the Elementary School level in Indonesia in general have not shown maximum results, this is because the social studies field includes subjects that are less attractive to students. This study aims to determine the effect of Problem Based Learning learning method and Conventional learning method as well as the ability to think logically towards learning outcomes in Social Sciences. This research was conducted on class VI students of the State Ibtidaiyah Madrasah in Ciputat, with a total of 60 students. This study uses treatment by level 2 x 2. The data analysis technique is the analysis of two-way variance (ANAVA). The results of the study showed that: (1) Student learning outcomes in social studies subjects taught using PBL learning method were higher than students taught using conventional method, (2) for students who have high logical thinking skills, the learning outcomes of students taught using the Problem Based Learning method are higher than those taught using conventional method, (3) for students who have low logical thinking skills, student learning outcomes are taught using the PBL method lower than students taught using conventional method.(4) there was an interaction effect between PBL learning method and logical thinking skills.